Mind your tones! The role of tonal morphology in Kwa action nominalization - Obed Nii Broohm; Chiara Melloni (Zeitschrift für Wortbildung)
In the typology of West African languages, tone has been noted to play crucial grammatical and lexical roles, but its function in word formation has been less systematically explored and remains to be fully understood. Against this backdrop, the present study seeks to examine the form and function of tonal morphology in the formation of action nominals in four Kwa languages spoken in Ghana, namely Akan, Gã, Lεtε, and Esahie, a relatively unexplored language of the Central Tano subgroup. Relying on data from both secondary and primary sources, we argue that tone raising is an important component of Kwa action nominalization, as it is found across different languages and derivational strategies. Specifically, while across the Kwa languages considered, tone raising tends to be an epiphenomenon of phonological conditioning, sometimes tone is the sole component of the nominalization operation or, as in Esahie, it concurs with the affix to the derivation, hence playing a morphological function.